Organized Labor and the Scope of International Specialization - Staiger, Robert W. (Journal of Political Economy, 1988)
This paper examines the interaction between union wages and the international pattern of production and trade. If union goods are heterogeneous in labor intensity, the introduction of an active union in the domestic country causes only the least labor-intensive range of union goods to be produced there, with goods of greatest labor intensity produced abroad because of the relatively high cost of domestic union labor. A narrowing of the scope of domestic union production will eliminate relatively labor-intensive goods, leading a rent-maximizing union to raise its union premium. The implications of this union behavior for comparative statics results are considered.